Nas rodas da macumba: os poemas de Aloísio Resende sob o signo da ancestralidade - Santos, Denilson Lima (2009)
Making a way among the literary production and discussions about religiosity, we’ve made a study of Zinho Faúla’s work — as also has been known our poet showed in this dissertation —, attempting to analyze the cultural Africans elements in Aloísio Resende’s poems (1900-1941), that deals with ‘Candomblé’ religion in Brazil and its relation with poetic aesthetics. To get it, we worked with Ana Angélica Vergne de Morais’ book: Aloísio Resende: poemas; com ensaios críticos e dossier — from what we analyzed thirteen poems which have Africans elements — these elements are faced as in mythical reality African tradition in Brazilian society as in valorization of African religious elements, from any African nation: Angola, Jeje, Nagô or Caboclo. In unveilment of word, tradition and text project themselves from poet’s mind and pen in memories’ wall, doing this way African inheritances reactivations that the poet born in Feira de Santana will use like voice of those who were suffocated. By the poetic word we discourse as event, like sign that bases to anyone’s voice that can be listened, in the other words, people excluded from society and literature. Even far away the writing system, of word’s world, some individuals resounds like resistance voice. Bringing it to poems’ analysis, we point to the social and literary questions that mold/molded the Brazilian cultural thought, as well as we set as limit, with identitary relations and with religious’ elements into Resende’s lyric poetry. This way, we meet with ourselves in the crossroads’ writing, this so emblematic and full of images place that point to faith’s vitality and the intellectual thought. Maybe we can, under Exu’s axé, dynamize the communication intending to the black’s place in Brazilian poetry may be always respected and comprehended as local where body, voice and experience transmit perpetuation of an ancestral poetry.